INTERNAL FACTORS INFLUENCING STUDENTS' SPEAKING ACHIEVEMENT - Pratiwi, Dian Fera (Institut Agama Islam Negeri (IAIN) Bone, 2024)
The purpose of this study was to discover and provide a descriptive description of the internal elements that influence the high speaking achievement of the students. To gain additional knowledge regarding the elements that contribute to the student's high speaking performance, this research utilised a case study approach supported by quantitative and qualitative data. The data resources included two kids from SMKN 8 who had achieved high success in speaking English, their parents, teachers, classmates, and the headmaster of SMKN 8 Makassar. Observation, interviews, inventories, the TOEIC test, and documentation reviews were the instruments that were utilised in this study. Analysis of the data was performed according to its nature. A qualitative analysis was performed on the information gathered through observation, interviews, and the reading of documents. According to the findings, the internal factors that contributed to the student's high achievement were as follows: (a) a highly positive attitude; (b) a high level of motivation; (c) a high level of interest; (d) a learning style that was very high and positive in both visual and auditory terms; (e) a metacognitive learning strategy; (f) a very low level of anxiety; and (g) a high level of English proficiency as well. After considering all of these elements, it became clear that the student's great accomplishment in speaking was unquestionably due to factors that were internal to the kid.Â